2014
DOI: 10.1039/c3cp53960a
|View full text |Cite
|
Sign up to set email alerts
|

Vibronic spectra of the p-benzoquinone radical anion and cation: a matrix isolation and computational study

Abstract: The electronic and vibrational absorption spectra of the radical anion and cation of p-benzoquinone (PBQ) in an Ar matrix between 500 and 40 000 cm À1 are presented and discussed in detail. Of particular interest is the radical cation, which shows very unusual spectroscopic features that can be understood in terms of vibronic coupling between the ground and a very low-lying excited state. The infrared spectrum of PBQ + exhibits a very conspicuous and complicated pattern of features above 1900 cm A notable exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 40 publications
2
21
0
2
Order By: Relevance
“…Thus, what Eq. (12) suggests is that the observed quasi-isotropic angular distribution behaviour, for many of the composite modes of bands I-III, is not the result of quantum interference effects but rather appears to be due to a "classical" superposition of the cross sections that make up the respective bands.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, what Eq. (12) suggests is that the observed quasi-isotropic angular distribution behaviour, for many of the composite modes of bands I-III, is not the result of quantum interference effects but rather appears to be due to a "classical" superposition of the cross sections that make up the respective bands.…”
Section: Resultsmentioning
confidence: 99%
“…Good reviews on this aspect can be found in the work of Itoh 5 and more recently in the work ofÓmarsson and Ingólfsson. 6 There have also been photoelectron, [7][8][9][10] and matrix isolation 12 studies in order to provide insights into the cationic structure of pBQ. The gas-phase photoabsorption spectrum in the visible [13][14][15] and UV 2,[16][17][18] spectral regions has been extensively studied, while in the vacuum ultraviolet (VUV) range, we note the low resolution study of Brint et al 19 and our own high resolution investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Low-energy dissociative electron interactions have been reviewed by Ómarsson and Ingólfsson, 6 while electronic excitation and ionisation processes have been studied by several different authors. 2,3,[7][8][9][10][11][12][13][14][15] Electron attachment processes have also been experimentally studied and some resonances identified, 16,17,18,19 with some of those resonances having recently been investigated through R-matrix 20 and "ab initio" electronic structure calculations of the p-BQ anion. 21,22 More recently, we have combined theoretical and experimental photoabsorption techniques to investigate the electronic excitedstate structure of pBQ, and their corresponding electron scattering cross sections, together with some elastic differential cross section calculations.…”
Section: Introductionmentioning
confidence: 99%
“…The spectroscopy of quinones has therefore attracted considerable attention over an extended period, with comprehensive reviews by Itoh 3 and more recently bý Omarsson and Ingólfsson. 4 While the electronic-state spectroscopy is complicated by a large number of closely lying (in energy) states, photo-, chemi-, and electron-impact ionization [5][6][7][8][9][10][11] investigations have helped to clarify the ordering of orbitals in the neutral species and its cationic structure. The anion states of pBQ and quinone derivatives have also been heavily studied, particularly through dissociative and non-dissociative electron attachment and electron scattering resonances.…”
Section: Introductionmentioning
confidence: 99%